Understanding the human person from the standpoint of the relational sociology (Memorandum: Memória e História em Psicologia, 2006)
This article deals with the question of how to conceptualize the human person as a living subject. The main difficulty consists on relating the single components of the human person to itself and to the external world. It is based on Margaret Archer’s thesis about the shortcoming of modernity in dealing with the human person and the need for a new perspective. We need a new scientific paradigm to understand how the human person can be both dependent on society and autonomous, possessing its own powers. Modernity looks for possible solutions by adopting conflicting epistemologies. Archer proposes a conception of human person, from the perspective of social realism, which grants humankind temporal priority, relative autonomy, and causal efficacy, in such a way that human persons become social beings with powers of transformative reflection and action that they bring to their social context, powers that are independent of social mediation.